Confronting Global Warming: Maine’s Multi-Sector Initiatives, 2003–2008 - Littell, David; Westerman, Gary; Burson, Malcolm (Maine Policy Review, 2008)
David Littell, Gary Westerman and Malcolm Burson describe Maine’s pioneering efforts in reducing greenhouse gas emissions, promoting energy efficiency, and developing less carbon-intensive and more sustainable energy sources. They discuss in particular the goals and accomplishments of the state’s Climate Action Plan and Maine’s participation in several multi-state and regional efforts, including the Regional Greenhouse Gas Initiative (RGGI).
Keywords: Maine; global warming; Maine climate change policy; greenhouse gas